Shuffling between Cladocopium and Durusdinium extensively modifies the physiology of each symbiont without stressing the coral host. Issue 24 (5th October 2021) - Abbott, Evelyn; Dixon, Groves; Matz, Mikhail
Abstract: As sea surface temperatures increase, many coral species that used to harbour symbionts of the genus Cladocopium have become colonized with the thermally tolerant genus, Durusdinium . Here, we asked how gene expression in the symbionts of one genus changes depending on the abundance of another symbiont genus within the same coral host, and what effect this interaction has on the host. Symbiont gene expression was overwhelmingly driven by whether the genus was the minority or the majority within the host, which affected 79% ( Durusdinium ) and 96% ( Cladocopium ) of all genes. Particularly strong effects in both genera were observed for photosynthesis components (upregulated in the minority state) and proteins putatively associated with cell motility (upregulated in the majority state). Importantly, there was no distinct gene expression signature associated with the mixed symbiosis state when both genera were represented in comparable proportions within the host, which could lead to more intense competition. The mixed symbiosis was also not associated with elevated host stress: in fact, after heat treatment, stress signatures were the lowest in mixed‐symbiosis corals compared to both Cladocopium ‐ and Durusdinium ‐dominated corals. In conclusion, during shuffling between Cladocopium and Durusdinium both symbiont genera go through extensive and largely reciprocal physiological transitions, but there is no evidence of intensifying antagonistic interactions that are detrimental to the host. Unless the mixed‐symbiosis corals in this study are not representative of the typical transition between Cladocopium and Durusdinium, the process of shuffling from one symbiont genus to another appears to be cost‐free for the coral host, and even appears to be associated with lower stress susceptibility. This raises optimism for the future corals, which will probably have to rely on symbiont shuffling more and more to withstand environmental challenges.